Positive genetic selection for gene disruption in mammalian cells by homologous recombination. - Sedivy, J M (1989)
Efficient modification of genes in mammalian cells by homologous recombination has not been possible because of the high frequency of nonhomologous recombination. An efficient method for targeted gene disruption has been developed. Cells with substitution of exogenous sequences into a chromosomal locus were enriched, by a factor of 100, using a positive genetic selection that specifically selects for homologous recombination at the targeted site. The selection is based on the conditional expression of a dominant selectable marker by virtue of in-frame gene fusion with the target gene. The dominant selectable marker was derived by modification of the Escherichia coli neo gene so that it retains significant activity in mammalian cells after in-frame fusion with heterologous coding sequences. In the example presented here, homologous recombinants were efficiently recovered from a pool in which the targeted gene was disrupted in 1 per 10,000 cells incorporating exogenous DNA.